GLP principles and their role in supporting pharmacokinetic and residue depletion studies for drug registration and licensing. Issue 5 (May 2016) - Croubels, Siska; De Backer, Patrick; Devreese, Mathias
Abstract : Good Laboratory Practice (GLP) is a quality system concerned with the organizational process and the conditions under which non‐clinical health and environmental safety studies are planned, performed, monitored, recorded, archived, and reported. This paper focuses on the GLP principles applicable for veterinary drug registration and licensing purposes. First, a general overview of the GLP requirements is given, followed by a more specific comparison and discussion of the analytical method validation parameters and acceptance criteria of different international guidelines applied in the context of veterinary drug pharmacokinetic and residue depletion studies. Finally, some needs with respect to method validation and new developments in pharmacokinetic and residue depletion studies are highlighted. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Good Laboratory Practice (GLP) is a quality system concerned with the organizational process and the conditions under which non‐clinical health and environmental safety studies are planned, performed, monitored, recorded, archived and reported. This paper focuses on the GLP principles with respect to analytical method validation, applicable to pharmacokinetic and residue depletion studies for veterinary drug registration and licensing purposes.